Composition of trace residues from the contents of 11th-12th century sphero-conical vessels from Jerusalem. - Carney D Matheson; Cory R Vickruck; Chris J McEvoy; Kim K Vernon; Robert Mason (PLoS ONE, 2022)
The residues from the internal surface of four archaeological ceramic sherds, excavated from the Armenian Gardens, Jerusalem were analysed to characterise the contents of the original vessel. The sherds derive from four small, thick-walled, sphero-conical vessels recovered from a destruction layer, dating between the 11th and 12th century, Jerusalem. The residue has been analysed using light microscopy, biochemical characterisation, gas chromatography mass spectroscopy, inductively coupled plasma atomic emission spectroscopy and cold vapour atomic fluorescence spectrometry. This analysis established the presence of various compounds including fatty acids and notable levels of mercury, sulphur, aluminium, potassium, magnesium, nitrates and phosphorous. The contents and probable functions of the four vessels were characterised from the residues on these sherds as different from each other, reflecting their different decoration, manufacture and ceramic typologies. One of these vessels contains residue that indicate the vessel held oils. The residue of the second vessel is consistent with either scented materials or medicinal contents, while a third probably contained medicinal material. The unique fourth sherd is from a stoneware sphero-conical vessel with very thick walls, no decoration and the residue supports the possibility it was used for the storage of chemicals or may have held the chemical ingredients for an explosive device, consistent with a medieval grenade. This residue analysis of Mamluk sphero-conical vessels provides insight into luxury items, medicines, technology and trade in medieval Jerusalem.